2021
DOI: 10.1002/anie.202104275
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Ferration of Aromatic Substrates through Intramolecular Sodium Mediation

Abstract: Exploiting cooperative effects between Na and Fe II centres present in tris(amide) ferrate complexes has led to the chemoselective ferration of pentafluorobenzene, benzene, toluene, anisole, and pyridine being realised at room temperature. The importance of this bimetallic partnership is demonstrated by neither the relevant sodium amide (NaHMDS or NaTMP) nor the Fe II amide Fe(HMDS) 2 efficiently metallating these substrates under the conditions of this study. By combining NMR studies with the isolation of key… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
2
27
3
Order By: Relevance
“…It should also be noted that the ferration of pentafluorobenzene by 1 is synergistic in origin since [Fe{N(SiMe 3 )Dipp} 2 ] on its own cannot selectively deprotonate this substrate; whereas the stronger base NaHMDS metallates this substrate albeit nonselectively generating a mixture of decomposition products including saline NaF. Formation of 4 can be envisaged to occur via a similar mechanism to that we have recently reported for [NaFe(HMDS) 3 ] (I), [23] with initial coordination of C 6 F 5 H to Na in 1 which induces the shift of one bridging HMDS amide to Na, facilitating the NaÀ H exchange which is immediately followed by a fast intramolecular trapping of the C 6 F 5 aryl anion by the Fe(II) centre (see Scheme S1 in Supporting Information).…”
Section: Reactivity Studies: Assessing Ferration Of C 6 F 5 H and Pyridinesupporting
confidence: 54%
See 4 more Smart Citations
“…It should also be noted that the ferration of pentafluorobenzene by 1 is synergistic in origin since [Fe{N(SiMe 3 )Dipp} 2 ] on its own cannot selectively deprotonate this substrate; whereas the stronger base NaHMDS metallates this substrate albeit nonselectively generating a mixture of decomposition products including saline NaF. Formation of 4 can be envisaged to occur via a similar mechanism to that we have recently reported for [NaFe(HMDS) 3 ] (I), [23] with initial coordination of C 6 F 5 H to Na in 1 which induces the shift of one bridging HMDS amide to Na, facilitating the NaÀ H exchange which is immediately followed by a fast intramolecular trapping of the C 6 F 5 aryl anion by the Fe(II) centre (see Scheme S1 in Supporting Information).…”
Section: Reactivity Studies: Assessing Ferration Of C 6 F 5 H and Pyridinesupporting
confidence: 54%
“…Our previous reactivity and computational studies on heteroleptic sodium ferrates containing both HMDS and TMP groups have shown that in solution [NaFe (TMP)(HMDS) 2 ] is actually in equilibrium with their homoleptic analogues [NaFe(HMDS) 3 ] (I) and [NaFe(TMP) 3 ]. [23] A similar process can be proposed to occur for 1 although in this case the steric demand imposed by the N(SiMe 3 )Dipp ligand could favour the cleavage of putative complex [NaFe(HMDS){N(SiMe 3 ) Dipp} 2 ] into its single-metal components NaHMDS and complex Fe{N(SiMe 3 )Dipp} 2 which can be detected spectroscopically (Scheme 1 and S13 in Supporting Information). It should also be noted that Mulvey has reported that related Na and K magnesiate complexes [M I Mg{N(SiMe 3 )Dipp} 2 (nBu)] 1 undergo redistribution in d 8 -THF solution furnishing the relevant alkalimetal amide and [M I N(SiMe 3 )Dipp] and BuMg{N(SiMe 3 )Dipp}.…”
Section: Preparing Sodium Ferrates With N(sime 3 )Dipp Ligandsmentioning
confidence: 72%
See 3 more Smart Citations